Prometeo o della rupe (Materiali di Estetica. Terza serie, 2017)
The myth of Prometeo is proposed by Kafka in four circular versions that from the betrayal to the grief, they merge in the forgetfulness and end in the inexplicable. Inexplicable as the leaving, the suffering and the destiny of the men, of which Prometeo is friend and accomplice.Keywords: Kafka; Prometheus; Myth; Grief